Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Kemampuan Pemecahan Masalah - Afdol, Afdol (Science and Education Journal (SICEDU), 2024)
This research aims to improve students' problem solving abilities in fraction material through the application of the Problem Based Learning learning model for class III UPT SD Negeri 009 Kebun Tinggi, Kampar Kiri Hulu District. This research was motivated by the low problem solving abilities of students, including students not being able to understand the problem, students not being able to plan mathematical models, and not being able to carry out planning correctly, completely and in detail. This research is classroom action research. The subjects in this research were one teacher and 11 students at UPT SD Negeri 009 Kebun Tinggi, Kampar Kiri Hulu District. Based on the results of research and data analysis, the application of the Problem Based Learning learning model can improve students' problem solving abilities. After the class action was carried out in cycle I, students' problem solving abilities increased slightly to 69.17% or classified as poor, and in cycle II students' problem solving abilities increased on average to 76.66% or classified as good. This means that the specified success indicators have been achieved. Thus, it can be concluded that through the Problem Based Learning learning model in mathematics subjects, fraction material can improve the problem solving abilities of students in class III UPT SD Negeri 009 Kebun Tinggi, Kampar Kiri Hulu District.